1996
DOI: 10.3109/00207459608987249
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler Assessment of Cerebral Flow Velocity at Rest and During Voluntary Movements in Young and Elderly Healthy Subjects

Abstract: Fifty-five healthy volunteers (thirty young and twenty-five elderly), all of them right-handed, were investigated by Transcranial Doppler monitoring mean flow velocity on the right and left middle cerebral artery at rest, during a motor task performed by the hand and in the following rest condition. In all cases the motor task induced an increase in bilateral mean flow velocity, but significantly greater on the opposite side middle cerebral artery in the task. The percentage increase in mean flow velocity comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 18 publications
6
26
0
3
Order By: Relevance
“…It is important to note that the BFV absolute or relative variations that can be observed during cognitive tasks are studied in most functional TCD works. However, and although the high temporal resolution of TCD is one of the key advantages of this technique, the instantaneous temporal evolution of BFV signals in subjects performing cognitive tasks has only been analyzed in some of the functional studies [20], which have found a maximum peak in BFV between 4 [180] to 20 s [181] after the initiation of a cognitive task, with an average peak after 6-9 s [31,158,149].…”
Section: 1 Bfv Signal Analysis In Functional Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…It is important to note that the BFV absolute or relative variations that can be observed during cognitive tasks are studied in most functional TCD works. However, and although the high temporal resolution of TCD is one of the key advantages of this technique, the instantaneous temporal evolution of BFV signals in subjects performing cognitive tasks has only been analyzed in some of the functional studies [20], which have found a maximum peak in BFV between 4 [180] to 20 s [181] after the initiation of a cognitive task, with an average peak after 6-9 s [31,158,149].…”
Section: 1 Bfv Signal Analysis In Functional Studiesmentioning
confidence: 99%
“…Given that the user had to navigate and control a joystick in the environment (with right arm movements), the differences could have their origin in these motor tasks (as subjects are right-handed, they move the right arm to control the joystick and variations in BFV are generated in the left hemisphere) [160,178,158].…”
Section: Comparison Of Bfv Variations In the Free Navigation Conditiomentioning
confidence: 99%
See 3 more Smart Citations